Mekanisme Produksi Siaran Langsung dan Tidak Langsung (Taping) untuk Meningkatkan Kualitas Siaran di Radio dan Televisi sebagai Media Dakwah - Erwan Effendi; Rahayu Nian Ramadhani; Rahmad Safii; Muhammad Furqon (Dakwatussifa: Journal of Da'wah and Communication, 2023)
Along with the development of the times of Indonesian society, especially people who are interested in television and radio, it is getting easier to receive information because of the development of programs on television and radio which are increasingly widespread and sophisticated. Television is the most widely used tool in accessing information and seeing various things that happen on radio. Therefore, many programs are produced, so methods and steps are needed so that the production of programs on television, both directly and indirectly, goes according to what is desired. Well, while radio is radio is electronic mass media that is the cheapest, easy to use, can be enjoyed anywhere and anytime. Radio has undergone a long process of development before becoming the mass communication medium it is today. The world of broadcasting continues to develop very rapidly without knowing boundaries and regions. Thanks to the development of communication / information technology, the flow of information can run very quickly, so as to be able to eliminate the distance in space and time between two places on earth and even between earth and outer space. This type of research is a qualitative research (qualitative research). This research method is documentation, namely data sources obtained from agencies or books (documents) related to this research problem. Radio is a form of mass media whose strength is as a disseminator of information that is very fast and able to reach. wide community. To achieve its target, namely listeners, something or program that will be displayed does not experience complex things. Compared to television, the difference is more complicated because radio media presents message content in audio form, while television presents message content in audiovisual form, motion and sync. Keywords : Radio,Television,Dakwah